KERAGAMAN KACANG-KACANGAN GENUS Vigna BERDASARKAN KARAKTER MORFOLOGIS DI KABUPATEN TIMOR TENGAH UTARA - Mau, Irene Konstantina; Seran, Yoseph Nahak; Bria, Emilia Juliyanti (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2023)
Vigna is a legume that has high nutritional and economic value. North Central Timor District is one of the areas on Timor Island which is the border of Indonesia and Timor Leste. The purpose of this study was to characterize the morphology of the species in the Vigna group which are commonly cultivated by local farmers. In this study, three species and one subspecies were obtained, namely rice beans (Vigna umbellata (Thumb) Ohwi & Ohashi), green beans (Vigna radiata L.), cowpea (Vigna unguiculata (L.) Walp), and long beans (Vigna unguiculata). ssp. sesquipedalis (L.) Verdc). The similarities in the morphological characters that can be seen are the type of epigeal germination, the shape of the round-hexagon stem, the shape of a butterfly flower with one of the crowns covering the pistil and stamens, and the shape of the pods, while the differences that are seen are quite a lot, namely in the presence/absence of pigmentation. hypocotyl, leaf shape, organ hairs, leaf color, corolla color, seed shape, seed color, and flowering time.